The Relationship between Parental Behavior and Premature Loss of Primary Teeth at SD No. 3 Benoa - Gusti Ayu Dinda Arya Kirana; Mia Ayustina Prasetya; Louise Cinthia Hutomo; Luh Wayan Ayu Rahaswanti (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2026)
Introduction: Untreated caries are the main cause of premature loss of primary teeth. Children generally prefer cariogenic foods, but this is not balanced by oral health maintenance behavior. This is because children do not understand the importance of maintaining their oral health. This is where parental behavior is needed to provide guidance and supervision to children in maintaining the health of their oral cavity. Based on this, the author is interested in examining the relationship between parental behavior and premature loss of primary teeth in students aged 6-8 years at SD No. 3 Benoa. Material and Methods: This study used an analytical observational method with a cross-sectional approach. The sample in this study was a dyad (parents and students) totaling 103 respondents. Result and Discussions: The study show that parental behavior is in the